2018
DOI: 10.1002/mp.12963
|View full text |Cite
|
Sign up to set email alerts
|

Current commercial techniques for MRI‐guided attenuation correction are insufficient and will limit the wider acceptance of PET/MRI technology in the clinic

Abstract: OVERVIEWWhole-body hybrid PET/MR imaging has been used since its introduction in 2010 in clinical and research settings for diagnosis, staging and restaging, assessment of response to treatment, and radiation therapy planning. However, the quantitative potential of PET/MRI is challenged by the lack of reliable and accurate MRI-guided attenuation correction (MRAC) owing to the lack of direct relationship between MRI signal, reflecting proton density and relaxation time properties, and electron density, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Though PET/MRI has been increasingly implemented in daily clinical applications, serious technical challenges remain in deriving accurate quantitative measurements. One major concern is the bias caused by current vendor implementations of MR-based AC methods and the resultant limitation in quantitative longitudinal therapy monitoring studies (Catana et al, 2018). We evaluate the reliability of the proposed method on quantifying tracer update changes over sequential scans and found that tracer uptake changes calculated on DL-AC PET matches the references well within 3% ("difference" rows in Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…Though PET/MRI has been increasingly implemented in daily clinical applications, serious technical challenges remain in deriving accurate quantitative measurements. One major concern is the bias caused by current vendor implementations of MR-based AC methods and the resultant limitation in quantitative longitudinal therapy monitoring studies (Catana et al, 2018). We evaluate the reliability of the proposed method on quantifying tracer update changes over sequential scans and found that tracer uptake changes calculated on DL-AC PET matches the references well within 3% ("difference" rows in Table 3).…”
Section: Discussionmentioning
confidence: 95%
“…However, it seems that there is still an ongoing discussion whether reasonably accurate methods have become commercially available, especially in challenging clinical applications [134], while the accuracy of MRAC can be considered adequate for the majority of routine clinical situations [47]. Furthermore, future efforts for standardization and quality control are important for accurate and robust results in both research and clinics and are needed for PET/MR as well [135].…”
Section: Status Of Pet/mr Attenuation Correction For Neuroimaging Formentioning
confidence: 99%
“…On the methodological side, the major obstacle slowing the widespread clinical adoption of PET/MR has been the challenge of generating accurate attenuation correction (AC) maps [2,3]. A correction must be applied to PET data to account for attenuation of the emitted photons prior to reaching the PET detectors [4,5].…”
Section: Technical Considerationsmentioning
confidence: 99%